HEPATOBLASTOMA REQUIRING LIVER TRANSPLANTATION. A CASE REPORT - Roxana-Cristina Mares; Mihaela Chincesan; Emoke Horvath; Horea Gozar; Cristina Oana Marginean (Amaltea Medical Publishing House, 2019)
Hepatoblastoma is a rare pathology in pediatric patients, occurring in 5-10/one million children. A two year old patient was admitted to our clinic for intense abdominal pain. On examination he presented a large mass in the right hypochondrium. Abdominal ultrasound and computer tomography (CT) revealed a large, solid hepatic tumor with thrombosis of the right portal vein. Serum alpha fetoprotein (AFP) level and thrombocyte number were increased. Liver biopsy was performed and the histopathological aspect was specific for an epithelial hepatoblastoma. Chemotherapy was initiated, followed by surgery in two steps: right portal branch ligation and subsequent tumor resection. Six months after surgery a relapse was suspected, confirmed by CT and elevated AFP levels. A "rescue" liver transplantation was performed and the patient is disease-free for three years. Elevated AFP and thrombocyte levels point to the diagnosis of hepatoblastoma. Liver transplantation is the final option for extensive, inoperable or relapsing tumors.